Distribution, management and diversity of yam local varieties in Brazil: a study on Dioscorea alata L. - Siqueira, Marcos Vinícius Bohrer Monteiro; Nascimento, Wellington Ferreira do; Silva, L. R. G.; Ferreira, A. B. [UNESP]; Silva, Edson Ferreira da; Ming, Lin Chau [UNESP]; Veasey, Elizabeth Ann (Instituto Internacional de Ecologia, 2014)
Widely spread in the tropics, yams were introduced into Brazil during the colonial period and are currently grown throughout the country. Despite its importance as a pharmacological and food source, there is a lack of studies describing how and where this tuber is grown in Brazil. The aim of this study was to provide an overview of the cultivation and distribution of Dioscorea alata in different Brazilian regions. A total of 63 farmers were visited in different municipalities and communities in four regions in the country: South, Southeast, Northeast and Midwest. Semi-structured interviews were conducted to collect socio-economic, use, management and diversity data for this crop. The majority of interviewers were men, married, with children, using retirement benefits and agriculture as income and family labour as the main support in the yam cultivation. A wide distribution of this species was found, with the occurrence of D. alata in the four sampled regions. A variety of vernacular names for this species was collected, differing according to the region where it is cultivated. Most farmers cultivate yams in fields, however an increased usage of home gardens for the cultivation of this tuber was found. Also, most farmers cultivate yams in association with other crops in areas of different sizes and slash and burn practices, although mostly disappearing, are still being used by many farmers. The results of this study provide more concrete data on the distribution and diversity of this important crop.

Amplamente difundido nos trópicos, o inhame entrou no Brasil na época da colonização e atualmente é cultivado em todo o país. Apesar de sua importância como cultura alimentícia e farmacológica, são raros os estudos que identifiquem como e onde esse tubérculo está sendo cultivado no Brasil. Este estudo teve como objetivo apresentar um panorama do cultivo e distribuição da espécie Dioscorea alata L. em diversas regiões do Brasil. Para tanto, foram visitados 63 agricultores em diferentes municípios, distribuídos entre o Sul, Sudeste, Nordeste e Centro-Oeste do país. Foram realizadas entrevistas semi-estruturadas, nas quais foram levantados dados socioeconômicos, bem como sobre o uso, manejo e diversidade dessa espécie. A maioria dos entrevistados eram homens casados, com filhos, que possuíam aposentadoria e a agricultura como principais fontes de renda. Constatou-se que a mão-de-obra familiar está bastante envolvida com o cultivo de inhame. Uma ampla distribuição da espécie foi observada, com a ocorrência de D. alata nas quatro regiões amostradas. Grande diversidade de nomes populares foi observada para a espécie neste estudo, com diferenças na nomenclatura popular em função das diferentes regiões onde a mesma é cultivada. A maioria dos agricultores cultiva inhame em roças, no entanto a importância dos quintais foi observada em vários municípios. Verificou-se também que a maioria dos entrevistados cultiva o inhame em consorciação com outras culturas e que a prática do pousio ainda é utilizada por muitos dos agricultores. Os resultados deste estudo permitiram gerar dados mais concretos sobre a distribuição e diversidade desta importante cultura.
Distribuição, manejo e diversidade de variedades locais de inhame no Brasil: um estudo em Dioscorea alata L
Keywords: diversidade agroecológica; Dioscorea; etnobotânica; conservação in situ; tubérculos; agroecological diversity; Dioscorea; ethnobotany; in situ conservation; tubers